Gender typicality in children's speech: a comparison of boys with and without gender identity disorder - Munson, B; Crocker, L; Pierrehumbert, J; Owen-Anderson, A; Zucker, K (AIP Publishing, 2015)
This study examined whether boys with gender identity disorder (GID) produced less prototypically male speech than control boys without GID, a possibility that has been suggested by clinical observations. Two groups of listeners participated in tasks where they rated the gender typicality of single words (group 1) or sentences (group 2) produced by 15 5–13 year old boys with GID and 15 age-matched boys without GID. Detailed acoustic analyses of the stimuli were also conducted. Boys with GID were rated as less boy-like than boys without GID. In the experiment using sentence stimuli, these group differences were larger than in the experiment using single-word stimuli. Listeners' ratings were predicted by a variety of acoustic parameters, including ones that differ between the two groups and ones that are stereotypically associated with adult men's and women's speech. Future research should examine how these variants are acquired.